![Pending changes are displayed on this page Pending changes are displayed on this page](/w/extensions/FlaggedRevs/frontend/modules/img/1.png)
There are no approved revisions of this page, so it may
not have been
reviewed.
This article page is a stub, please help by expanding it.
The cubic formula gives the roots of any cubic equation
The three (distinct or not) roots are given by (Cardano published a similar formula in 1545)
-
![{\displaystyle x=p+{\sqrt[{3}]{q-Q}}+{\sqrt[{3}]{q+Q}},\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/5f27c627e9eab22ba6d49b5acfff7c7c0678c7c4)
where
-
![{\displaystyle Q={\sqrt {q^{2}+(r-p^{2})^{3}}},\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/67ed0db138eedec5bf6419ce592587cba5042be1)
-
![{\displaystyle p=-{\frac {b}{3a}},\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/4e0a96bc73cfae4bb78c28818738cb3e38770d4c)
-
![{\displaystyle q=p^{3}-\left({\frac {pc+d}{2a}}\right),\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/8aeb0a91c30b025c0c991f22d018b811be40a8d0)
-
![{\displaystyle r={\frac {c}{3a}}.\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/bd74d0ea3bd3851c7a1285c2eee42ddd46f134d9)
Equivalently, the three (distinct or not) roots of
with
and
, may be written as
![\displaystyle { x = B + \sqrt[3]{q - Q} + \sqrt[3]{q + Q}, } {\displaystyle {\begin{array}{l}\displaystyle {x=B+{\sqrt[{3}]{q-Q}}+{\sqrt[{3}]{q+Q}},}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/c99f25c4b10bc050219f1ec95640a6a619afd4ae)
where
![\displaystyle { Q = \sqrt{q^2 + (C - B^2)^3}, } {\displaystyle {\begin{array}{l}\displaystyle {Q={\sqrt {q^{2}+(C-B^{2})^{3}}},}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/3e057cf19f2ee13791a5e1962c724b673b5d2e64)
![\displaystyle { q = B^3 - \left( \frac{3BC - D}{2} \right). } {\displaystyle {\begin{array}{l}\displaystyle {q=B^{3}-\left({\frac {3BC-D}{2}}\right).}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/ac298edae0e454a73f26ad46a8e1b3f2e541bf41)
Completing the cube
The three roots are obtained by completing the cube, i.e.
![\displaystyle { \left( x + \tfrac{b}{3a} \right)^3 - 3 \left( \tfrac{b}{3a} \right)^2 \, x - \left( \tfrac{b}{3a} \right)^3 + \tfrac{c}{a} \, x + \tfrac{d}{a} = 0 = \left( x - B \right)^3 - 3 B^2 x + B^3 + 3 C x - D,\quad a \ne 0, } {\displaystyle {\begin{array}{l}\displaystyle {\left(x+{\tfrac {b}{3a}}\right)^{3}-3\left({\tfrac {b}{3a}}\right)^{2}\,x-\left({\tfrac {b}{3a}}\right)^{3}+{\tfrac {c}{a}}\,x+{\tfrac {d}{a}}=0=\left(x-B\right)^{3}-3B^{2}x+B^{3}+3Cx-D,\quad a\neq 0,}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/d7f35b47b28b8f44e1925571b58c5f67f2b23edf)
or, letting
,
![\displaystyle { y^3 - 3 \left( \tfrac{b}{3a} \right)^2 \, \left( y - \tfrac{b}{3a} \right) - \left( \tfrac{b}{3a} \right)^3 + \tfrac{c}{a} \, \left( y - \tfrac{b}{3a} \right) + \tfrac{d}{a} = 0 = y^3 - 3 B^2 (y + B) + B^3 + 3 C (y + B) - D,\quad a \ne 0, } {\displaystyle {\begin{array}{l}\displaystyle {y^{3}-3\left({\tfrac {b}{3a}}\right)^{2}\,\left(y-{\tfrac {b}{3a}}\right)-\left({\tfrac {b}{3a}}\right)^{3}+{\tfrac {c}{a}}\,\left(y-{\tfrac {b}{3a}}\right)+{\tfrac {d}{a}}=0=y^{3}-3B^{2}(y+B)+B^{3}+3C(y+B)-D,\quad a\neq 0,}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/6a913eae66d63dc3bfae81ba0fe62ac3dad8c1b2)
yielding the depressed cubic equation
![\displaystyle { y^3 + 3 (C - B^2) y - 2 B^3 + 3 BC - D = 0 = y^3 + 3 R y + S, } {\displaystyle {\begin{array}{l}\displaystyle {y^{3}+3(C-B^{2})y-2B^{3}+3BC-D=0=y^{3}+3Ry+S,}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/f000e724e09e09df70db2efbbe1c854d8f532a6c)
with
and
.
Solving the depressed cubic equation with Vieta's substitution
The depressed cubic equation
-
![{\displaystyle y^{3}+3Ry+S=0\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/bd65458fd554d1ef2628049a90e40f894dfc419f)
is solved by doing Vieta's substitution
-
![{\displaystyle y=w-{\frac {R}{w}},\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/97bfc50a167aa09cb9d2afc83217c4f7bfae7b44)
yielding
-
![{\displaystyle w^{3}+S-{\frac {R^{3}}{w^{3}}}=0.}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/65556076fd483f321f4ecf9fe674b2abeaf9eaa4)
Multiplying by
, it becomes a
sextic equation in
, which happens to be a quadratic equation in
-
![{\displaystyle w^{6}+Sw^{3}-R^{3}=0=z^{2}+Sz-R^{3},\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/456e64c6fdcf3a4db5d950b5c6354d6ac4b4a74a)
which is solved with the quadratic formula to get
-
![{\displaystyle {\begin{aligned}w^{3}&={\frac {-S\pm {\sqrt {S^{2}+4R^{3}}}}{2}}={\frac {(2B^{3}-3BC+D)\pm {\sqrt {(2B^{3}-3BC+D)^{2}+4(C-B^{2})^{3}}}}{2}}\\&=q\pm {\sqrt {q^{2}+(C-B^{2})^{3}}}=q\pm Q,\end{aligned}}\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/5b7328e96344cac011b39af9489d4bf131ea24e1)
with
![\displaystyle { Q = \sqrt{q^2 + (C - B^2)^3}, } {\displaystyle {\begin{array}{l}\displaystyle {Q={\sqrt {q^{2}+(C-B^{2})^{3}}},}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/3e057cf19f2ee13791a5e1962c724b673b5d2e64)
If
,
and
are the three
cube roots for each of the two solutions in
, then
-
![{\displaystyle {y_{i}}_{\pm }={w_{i}}_{\pm }-{\frac {R}{{w_{i}}_{\pm }}}={w_{i}}_{\pm }-\left({\frac {C-B^{2}}{{w_{i}}_{\pm }}}\right),\quad 1\leq i\leq 3,\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/e01fff35bdf08f04c2adb554ca4821946bf68841)
and
![\displaystyle { {x_i}_{\pm} = B + {y_i}_{\pm} = B + {w_i}_{\pm} - \frac{R}{ {w_i}_{\pm} } = B + {w_i}_{\pm} - \left( \frac{C - B^2}{ {w_i}_{\pm} } \right), \quad 1 \le i \le 3. } {\displaystyle {\begin{array}{l}\displaystyle {{x_{i}}_{\pm }=B+{y_{i}}_{\pm }=B+{w_{i}}_{\pm }-{\frac {R}{{w_{i}}_{\pm }}}=B+{w_{i}}_{\pm }-\left({\frac {C-B^{2}}{{w_{i}}_{\pm }}}\right),\quad 1\leq i\leq 3.}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/2fee9125e5a061491967b0e0973aedd7dbb13c75)
Thus, the three (distinct or not) roots are given by (see how the three roots of the two solutions are used in pairs, yielding three roots)
![\displaystyle { x = B + \sqrt[3]{q \pm Q} + \left( \frac{B^2 - C}{\sqrt[3]{ q \pm Q} } \right) = B + \sqrt[3]{q \pm Q} + \sqrt[3]{q \mp Q}, } {\displaystyle {\begin{array}{l}\displaystyle {x=B+{\sqrt[{3}]{q\pm Q}}+\left({\frac {B^{2}-C}{\sqrt[{3}]{q\pm Q}}}\right)=B+{\sqrt[{3}]{q\pm Q}}+{\sqrt[{3}]{q\mp Q}},}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/2a5115d27fbcdabba8877cfedf75bee8b803cc40)
where
, since
.
Finally, the three (distinct or not) roots of
a x 3 + b x 2 + c x + d = 0, a ≠ 0, |
may be written as
![\displaystyle { x = B + \sqrt[3]{q - Q} + \sqrt[3]{q + Q}, } {\displaystyle {\begin{array}{l}\displaystyle {x=B+{\sqrt[{3}]{q-Q}}+{\sqrt[{3}]{q+Q}},}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/c99f25c4b10bc050219f1ec95640a6a619afd4ae)
where
![\displaystyle { Q = \sqrt{q^2 + (C - B^2)^3}, } {\displaystyle {\begin{array}{l}\displaystyle {Q={\sqrt {q^{2}+(C-B^{2})^{3}}},}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/3e057cf19f2ee13791a5e1962c724b673b5d2e64)
![\displaystyle { q = B^3 - \left( \frac{3BC - D}{2} \right), } {\displaystyle {\begin{array}{l}\displaystyle {q=B^{3}-\left({\frac {3BC-D}{2}}\right),}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/b482fffefed34298d486a2badd06253e540d153d)
with
and
.
Vieta's formulas for the cubic
Vieta's formulas for the cubic
-
![{\displaystyle (x-x_{1})(x-x_{2})(x-x_{3})=0,\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/5fdd73499750b68dc338b0081bf13ccfa7406242)
gives a system of three equations in three variables (which are the three roots)
![\displaystyle { \begin{align}
x_1 + x_2 + x_3 &= - \frac{b}{a} = 3 B, \\
x_1 \cdot x_2 + x_1 \cdot x_3 + x_2 \cdot x_3 &= + \frac{c}{a} = 3 C, \\
x_1 \cdot x_2 \cdot x_3 &= - \frac{d}{a} = D.
\end{align} } {\displaystyle {\begin{array}{l}\displaystyle {\begin{aligned}x_{1}+x_{2}+x_{3}&=-{\frac {b}{a}}=3B,\\x_{1}\cdot x_{2}+x_{1}\cdot x_{3}+x_{2}\cdot x_{3}&=+{\frac {c}{a}}=3C,\\x_{1}\cdot x_{2}\cdot x_{3}&=-{\frac {d}{a}}=D.\end{aligned}}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/66c45330159fd4d7fe4ffce1a2c261ed81aa0ed5)
By dividing the third equation into the second equation, one obtains a formula for the harmonic sum of the roots
![\displaystyle { \frac{1}{x_1} + \frac{1}{x_2} + \frac{1}{x_3} = - \frac{c}{d} = 3 \frac{C}{D}. } {\displaystyle {\begin{array}{l}\displaystyle {{\frac {1}{x_{1}}}+{\frac {1}{x_{2}}}+{\frac {1}{x_{3}}}=-{\frac {c}{d}}=3{\frac {C}{D}}.}\end{array}}}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/10b3ebeff255b3e9634acc78bd99efd2ebd21243)
See also
External links